Allergic and non-allergic rhinitis in swimmers: clinical and cytological aspects. Issue 1 (27th June 2010) - Gelardi, Matteo; Ventura, Maria Teresa; Fiorella, Raffaele; Fiorella, Maria Luisa; Russo, Cosimo; Candreva, Teresa; Carretta, Antonella; Passalacqua, Giovanni
Abstract : Background: Rhinitis, either allergic or non-allergic, is frequent in athletes, particularly in swimmers. In this latter case, exposure to chlorine in swimming pools seems to play a relevant role, since it can exacerbate a pre-existing allergic rhinitis (AR) or produce a non-specific irritation. The aim of this study was to detail the clinical and cytological characteristics of rhinitis in swimmers, and to assess the possible role of chlorine-induced symptoms. Methods: Elite swimmers with rhinitis symptoms underwent a complete diagnostic work-up, including allergy testing, nasal cytology and anterior rhinomanometry. Those evaluations were repeated after 1 month of use of a nasal clip during swimming. A matched group of asymptomatic swimmers was also studied. A total of 74 swimmers (54 symptomatic and 20 controls), with an age range of 9–21 years, were studied. In the control group, only mild and non-specific findings were observed, and only two had a positive skin test. Results: In the symptomatic group, 24 (44%) had AR, and 19 (35%) had a predominant neutrophilic inflammation. The use of a nose clip reduced cellular infiltration and nasal resistances only in the subjects with neutrophilic rhinitis, whereas a clinical improvement was seen also in AR. Conclusion: A neutrophilic rhinitis occurs in a large proportion of swimmers. This seems to be irritative in its nature and can be prevented by avoiding the direct contact with chlorinated water.